2019
DOI: 10.1002/chem.201900549
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Regio‐ and Stereoselective Alkene Sulfenoamination for 1,4‐Benzothiazine Synthesis

Abstract: An alkene sulfenoamination reaction with 2‐aminothiophenol is developed using iodide catalysis. This reaction renders access to useful 1,4‐benzothiazines with good functional group compatibility including both electron‐donating and electron‐withdrawing substituents. The reaction is proposed to proceed through an inversion of the polarity of the thiol functionality. Our mechanistic studies reveal that both thiiranium and thiyl radical pathways are plausible and that the disulfide reagent can also function as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…of K 2 S 2 O 8 was sufficient in this reaction (entries [17][18][19]. Besides, the optimal reaction temperature was 80 °C after the examination of the reaction temperature (entries [19][20][21][22]. Furthermore, controlled experiment in the absence of catalyst (entry 23) or oxidant (entry 24) revealed that both catalyst and oxidant are crucial in this reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of K 2 S 2 O 8 was sufficient in this reaction (entries [17][18][19]. Besides, the optimal reaction temperature was 80 °C after the examination of the reaction temperature (entries [19][20][21][22]. Furthermore, controlled experiment in the absence of catalyst (entry 23) or oxidant (entry 24) revealed that both catalyst and oxidant are crucial in this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…[18] However, these works were suffered with several drawbacks, including narrow substrates scope and harsh reaction conditions. As a part of our continuously efforts in the oxidative dehydrogenative functionalization of CÀ H bond of alkenes, [19] herein, we proposed a metal-free aerobic oxidative cross-dehydrogenative coupling reaction of alkenes with thiophenols for allylic thioethers synthesis (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…We have long been interested in developing “-onium”-based alkene functionalization reactions that clearly benefit from the use of widely available alkene starting materials . Morpholine is a highly valuable motif in bioactive molecules, and numerous synthetic strategies targeting this motif have been developed .…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al demonstrated a three-component transition-metalfree aerobic method using a KI/DMSO/O 2 system for the facile generation of iminobenzo-1,4-thiazines in moderate to good yield [31]. 3,4-Dihydro-2H-benzo-1,4-thiazine derivatives 6 were also successfully prepared [32]. The protocol, using NaI as a catalyst and K 2 S 2 O 8 as an oxidant, tolerated a broad range of substrates with good stereoselectivity.…”
Section: Introductionmentioning
confidence: 99%